What is the perceived impact of Covid-19 regulations pertaining to entry-level employees in the office interior design environment? - Maartens, Maresa (The IIE, 2022)
The purpose of this study is to determine the perceived impact of Covid-19 regulations pertaining to entry-level employees in the office interior design environment. More specifically, whether the employees work performance and well-being are affected by the implementation of the Covid-19 protocols. The study aims to explore what makes the ideal office environment through investigating the design theory of “prospect and refuge”. Furthermore, evidence-based design will be explored to further understand the surrounding debates of open-plan offices versus cellular office layouts, and lastly, Indoor Environment Quality (IEQ) will be explored to investigate the impact of the office interior environment on employee performance and well-being. The study reviews existing literature to gain a deeper understanding of the problem in a South African context, where South African office spaces are discussed pre- and post-Covid-19. Two data collection methods were used in the qualitative study, namely, focus groups and interviews, in hopes to determine the perceived impact of Covid-19 regulations pertaining to entry-level employees. As a result, four key themes were derived from the findings namely, the office layout and productivity; the ideal office environment; Covid-19 and the office environment; and offices that support remote working. The exploratory study aims to possibly contribute to a deeper understanding of the phenomenon. Furthermore, the study could prove beneficial to organisations as a decrease in workplace productivity could be detrimental to the business. Employees could benefit from the research as an improvement could be made as the research findings prove that Covid-19 regulations do impact their perceived well-being and performance. The anticipated contribution of the study is to add to the existing body of knowledge regarding office layouts and to contribute to the elimination of a gap in the present literature regarding the new challenges faced in the work environment due to the global pandemic. Furthermore, the study can be further explored where more research can be conducted on flexible office environments.
Keywords: Pandemic; Well-being; Performance; Productivity; Offices